Respuesta :
We observe that we have a polynomial of the form:
ax2 + bx + c
Therefore, to complete the square, we must use the following formula:
a (x + (b / 2a)) ^ 2 + c - (b ^ 2 / 4a)
Thus,
Step 1:
We define:
a = 5
b = 15
c = -4
Step 2:
we use the formula:
5 (x + (15 / (2 * 5))) ^ 2 + (-4) - ((15) ^ 2 / (4 * 5))
5 (x + (15 / (2 * 5))) ^ 2 - 15.25
5 (x + 1.5) ^ 2 - 15.25
5 (x + 3/2) ^ 2 - 61/4
Answer:
Gio should do first:
a (x + (b / 2a)) ^ 2 + c - (b ^ 2 / 4a)
a = 5
b = 15
c = -4
ax2 + bx + c
Therefore, to complete the square, we must use the following formula:
a (x + (b / 2a)) ^ 2 + c - (b ^ 2 / 4a)
Thus,
Step 1:
We define:
a = 5
b = 15
c = -4
Step 2:
we use the formula:
5 (x + (15 / (2 * 5))) ^ 2 + (-4) - ((15) ^ 2 / (4 * 5))
5 (x + (15 / (2 * 5))) ^ 2 - 15.25
5 (x + 1.5) ^ 2 - 15.25
5 (x + 3/2) ^ 2 - 61/4
Answer:
Gio should do first:
a (x + (b / 2a)) ^ 2 + c - (b ^ 2 / 4a)
a = 5
b = 15
c = -4
Answer: A
Step-by-step explanation:
The correct answer is the first option which is to isolate the constant. Completing the square is done as follows:
1. Write the equation in a way that the constants are in the right side while the terms with x are on the left.
5x2 + 15x = 4
2. Make sure that the coefficient of the x^2 term is 1.
5(x^2 + 3x) = 4
3. Adding a term to both sides that will complete the square in the left side. This is done by dividing the coefficient of the x term by 2 and squaring it. Note: The same amount should be added to the right side to balance the equation.
5(x^2 + 3x + 9/4) = 4 +45/4
5(x+3/2)^2 = 61/4